Pengaruh Ukuran Perusahaan, Profitabilitas dan Komite Audit Terhadap Pengungkapan Corporate Social Responsibility - Muhammad Rivandi; Ridho Juanda Putra (Owner : Riset dan Jurnal Akuntansi, 2021)
Corporate Social Responsibility is one of the social programs raised by the company in order to build good techniques for the wider community, namely in the form of social activities that are very helpful for the wider community in facing the realities that occur today and provide convenience for what they need. CSR is used as a component of the company's business assessment. This study aims to determine and analyze the effect of company size, profitability and audit committee variables partially on CSR disclosure, as well as to determine which variable has the most dominant influence on CSR disclosure in food and beverage sub-sector manufacturing companies. The data processed is secondary data from the annual reports of 11 food and beverage sub-sector manufacturing companies listed on the IDX in 2015-2019 which were taken through purposive sampling. The method used in this research is panel data regression analysis method using Eviews version 8.0. The results of this study indicate that: company size has a negative effect on CSR disclosure, profitability and the audit committee does not have a significant effect on CSR disclosure.